A Comparative Study between the Standards of Accreditation of Basic Hospitals Issued by the Health Care Accreditation Council (HCAC) and Indicators for the Health Performance Issued from the Iraqi Ministry of Health and the Federal Financial Control Burea - Ahmed Abdulsattar Hameed; Wafaa Abd Al-Ameer Hassan (Journal of Madenat Alelem University College, 2020)
The health situation in Iraq has many problems which are represented mainly by level providing health care by health institutions. The health service is considered one of the most important services needed by human because of their association with their life and this service is closely related to human performance and the extent to which the beneficiary accepts the performance level of the health service provided. So many international health organizations have begun to develop reliable standards for health institutions. This focused on the beneficiary of the health service (patient) in addition to the technological, technical and administrative aspects related to health care. Through this research, we seek to explain the differences and similarities between the standards of accreditation of basic hospitals issued by the Health Care Accreditation Council (HCAC) and indicators for measuring the health performance of hospitals in the Iraqi Ministry of Health accredited and indicators for measuring the health performance of the Federal Financial Control Bureau and a statement of shortcomings in those indicators.